British constitution and politics / by J. Harvey and L. Bather - "Harvey, J." (London, 1983)
In writing this book, our primary object has been to provide a textbook covering the british system of government.It has been designed particularly for students of 'British Constitution' in the general certificate of education, for those taking professional examination such as the Diploma in Public administration.
Keywords: "Great Britain, constitution"